2008
DOI: 10.1111/j.1574-6968.2008.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of outer membrane lipopolysaccharides in the protection of Salmonella enterica serovar Typhimurium from desiccation damage

Abstract: The ability to survive desiccation between hosts is often essential to the success of pathogenic bacteria. The bacterial outer membrane is both the cellular interface with hostile environments and the focus of much of the drying-induced damage. This study examined the contribution of outer membrane-associated polysaccharides to the survival of Salmonella enterica serovar Typhimurium in air-dried blood droplets following growth in high and low osmolarity medium and under conditions known to induce expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…27,28,38 However, Gram-negative Salmonella has also been shown to survive in low moisture content conditions 26 due at least in part to the water-retaining capacity of expressed lipopolysaccharides. 39 This is consistent with observed tailing of the S. typhimurium survivor curves at low relative humidity in the present study.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…27,28,38 However, Gram-negative Salmonella has also been shown to survive in low moisture content conditions 26 due at least in part to the water-retaining capacity of expressed lipopolysaccharides. 39 This is consistent with observed tailing of the S. typhimurium survivor curves at low relative humidity in the present study.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…Induction of other genes in dehydrated Bradyrhizobium cells, such as those involved in synthesis of pili, flagella, exopolysaccharides, and trehalose, was not observed in our study. Similarly, our transcriptomic analysis did not identify several genes previously reported to be involved in desiccation tolerance of Salmonella, such as the O-antigen capsule synthesis genes yihO and yihQ (29), the O-chain assembly gene wzx (28), or genes involved in synthesis of curli and cellulose (72). One possible explanation is that transcription of these genes was also induced in our control cells incubated in SDDW.…”
Section: Figmentioning
confidence: 53%
“…Several studies have investigated desiccation tolerance in Salmonella. Extracellular components such as thin aggregative fimbriae and cellulose as well as the lipopolysaccharide (LPS) core unit are apparently required for optimal desiccation tolerance (28,29,72). Exposure of Salmonella to desiccation stress increased cross-tolerance to a number of other stresses, including high temperature, osmotic stress, and biocides (30).…”
mentioning
confidence: 99%
“…White et al (24) suggested the involvement of fimbriae and cellulose in the enhancement of long-term survival of Salmonella under drying conditions, and Gibson et al (7) suggested an important role of Oantigen capsule in the regulation of dry-resistance by S. Enteritidis through the formation of a fimbriae-and celluloseassociated extracellular matrix. Recently, Garmiri et al (6) suggested a role for lipopolysaccharides in the protection of Salmonella Typhimurium from desiccation-related damage. It is not known whether SEp22, Salmonella Dps, participates in the regulation of extracellular matrix formation or lipopolysaccharide synthesis, as nutrients such as LB medium or casamino acids induced SEp22 expression in minimal medium in our previous studies (22).…”
Section: Discussionmentioning
confidence: 99%
“…To date, dry-resistant phenotypes of Salmonella have been studied in relation to food-protection (3,4,12,23), biofilm formation (2), morphological changes (11,25,26) and stress responses (9,12). Many of these studies have focused on changes in a viable but non-culturable state (12,14), including aggregation (26), fimbriae and cellulose (24), or lipopolysaccharide (6,7). However, the assay systems used in these experiments require a long incubation period before any estimation of changes.…”
mentioning
confidence: 99%